Case Study of an African American Woman With Heart Failure: Ethical and Palliative Care Considerations. Issue 4 (6th August 2022) - Hendricks-Ferguson, Verna L.; Stallings, Devita T.
Abstract : Heart failure affects an estimated 6.2 million adults in the United States. African Americans have a higher incidence of heart failure at an earlier age and more rapid disease progression than other ethnicities. African Americans also often receive lower-quality, end-of-life care and less often receive palliative and advanced-care planning than Whites. Several barriers exist for effective heart failure evaluation and treatment among African Americans, including ineffective patient-provider communication, mistrust, health care providers' lack of understanding of palliative care services, and potential downstream effects of social determinants of health (eg, access barriers to healthy food and community health promotion resources). Despite the recognized benefits of palliative care, few adults with heart failure are receiving early discussions about palliative and advanced care planning to ensure delivery of goal-concordant care. This article presents a fictitious case study focused on an African American woman, Ms T, with heart failure who has been given 6 months to live. Racial inequities are presented surrounding Ms T's inadequate access to necessary health care resources and in receiving delayed communication about palliative and advanced care services. The case study also highlights ethical principles of concern, the role of an interdisciplinary team approach for patients with heart failure, and the advocacy role of nurses.